Proxy-led accountability for natural resource extraction in rentier states. Issue 1 (2nd January 2023) - Kramarz, Teresa; Mason, Michael; Partzsch, Lena
ABSTRACT: The resource curse literature suggests that, in fragile states dependent on natural resource rents, structures of public accountability are weak because of an elite-controlled political economy indifferent to social and ecological interests. We examine accountability claims made by non-domestic proxy actors, holding governments and corporations accountable on behalf of communities adversely affected by natural resources extraction. This conceptualization is suggested by proxy-led transnational mobilization against mining-related damage in the Democratic Republic of the Congo. We identify an 'hourglass' structure of proxy actor engagement with affected communities: In a first phase, proxies rely on public mechanisms to define standards remotely. In a second phase, proxies 'narrow' the gap by seeking compliance information from affected communities. However, in a third phase, this gap 'widens' again when proxies remotely seek sanctions against responsible actors. We discuss the applicability of this heuristic framework to proxy-led accountability practices in other natural resource-dependent rentier states.